Chimarrão, terere and mate-tea in legitimate technology modes of preparation and consume: A comparative study of chemical composition, antioxidant, anti-inflammatory and anti-anxiety properties of the mostly consumed beverages of Ilex paraguariensis St. Hil. (28th October 2021) - Mesquita, M.; Santos, E.; Kassuya, C.A.; Salvador, M.J.
Abstract: Ethnopharmacological relevance: Ilex paraguariensis St. Hil. (Aquifoliaceae) is a medicinal plant widely used by South American populations for centuries and is popularly attributed to stimulating and detoxifying properties. Nowadays, their consume traditionally occurs through three different beverages: chimarrão, terere and mate-tea. Aim of the study: Although its composition and properties are well studied, literature lacks work comparing the potential of their extracts obtained by a legitimate preparation mode of their popular beverages. Therefore, the purpose of this research is to investigate changes in chemical composition, antioxidant activity, anti-inflammatory efficacy and anxiolytic effect from lyophilized aqueous extracts obtained simulating the legitimate popular preparation mode of chimarrão, terere and mate-tea. Materials and methods: In this work, were investigated differences related to preparation technology and dry material used through chemical composition analysis, with the lyophilized aqueous extracts obtained simulating the chimarrão, terere and mate-tea preparation. The chemical composition analysis comprises the total soluble phenolics content, chemical profiles by HPLC-ESI-MS/MS, and quantitative component detection by HPLC-UV/DAD. Moreover, evaluations of comparative antioxidant activity of the extracts (DPPH and ORACFL assays), anti-inflammatory efficacy and anxiolytic effect were performed in vivo . Results: Our results showed that chimarrão extracts presented a richer composition in terms of phenolic compounds and purine alkaloids, and better antioxidant activity when compared to the other extracts. In pleurisy test, all products showed anti-inflammatory properties in the dose of 60 mg/kg. In the anxiolytic evaluation, although all extracts presented some effect, chimarrão and terere were better than mate-tea in general. No sign of toxicity was observed. Conclusions: Our findings support that the beverage made as chimarrão has the best composition and the most promising properties overall. Graphical abstract: Image 1 Highlights: Ilex paraguariensis is a medicinal herb traditionally consumed for centuries in three forms chimarrão, terere and mate tea. Comparative chemical composition and antioxidant, anti-inflammatory and anti-anxiety properties of three yerba mate extracts. Extracts presented constant chemical profile and HPLC tests show chimarrão has richer composition. Extracts showed considerable antioxidant capacity in vitro and good anti-inflammatory properties in vivo . Anxiolytic effects by Yerba mate extracts were detected in behavior tests.